The neutralization of the messianic idea in medieval jewish rationalism - Shṿarts, Dov (Hebrew Union College annual / Jewish Institute of Religion, 1993)
Maimonides moderated the image of the messianic idea in two ways. First, he introduced the idea as a matter of educational encouragement for the masses. Second, he negated any orientation in the messianic concepts (Gan-Eden, Resurrection, World-to-come etc.), thus nullifying any attempt to reconstruct a well-defined messianic theory. As seems clear, Maimonides himself did not doubt the reality of the messianic events; but Maimonides' disciples for the next two centuries turned the messianic idea into a symbol and parable by a continuing process of allegorical interpretation of the Bible and Aggadah. Thus, according to the medieval rationalists (Samuel and Moses ibn Tibbon, Levi ben Abraham, Samuel ibn Zarza, Prat Maimon, etc.), all messianic concepts became hints and allusions to the intellectualistic development of man. Furthermore, the universal character of the messianic epoch as related to the human race or even to nature in its wholeness was changed by the rationalists to a totally individual one. The Messianic process applied thus only to the individual. The struggle between matter and intellect; actualization of the material intellect; conjunction of the material intellect with the active intellect as the ultimate felicity of man — all these were emphasized as the inner meaning and truth of messianism. The present study describes these phenomena, i.e., the neutralization of the messianic idea, in the following concepts: Messianic Activities, the Messiah, the End of Days and Resurrection.